Implementing an open source Information Retrieval Portal. - Gue, Kia Wee. (2008)
To design and implement an Information Retrieval Portal, which serves as a web-based source code sharing repository and information management environment for both students and academic staff to share knowledge in the field of information retrieval. The portal was implemented using Jetspeed, which is an open source project from the Apache Software Foundation.